2019
DOI: 10.7759/cureus.5313
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Article Citations by Authors from American Institutions in Major Radiology Journals

Abstract: ObjectiveTo investigate gender difference patterns in article citations, by first and last authors, in four radiology journals.Materials and methodsArticles by authors published in four major radiology journals from 1984, 1994, 2004, and 2014 were categorized into 12 subspecialties. The number of citations, references used, co-authors, and length of the article (number of pages) were documented. The genders of first/last authors were determined. Data were analyzed using chi-square and logistic regression.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…For example, in an analysis from 2011 to 2015 of the medium- to high-ranked journals Radiology , Academic Radiology , and AJR, Campbell et al [ 7 ] attributed 30% of FA and 25% of SA to women. A study of the four medium- to high-ranking journals Radiology , EJR, Journal of Computer Assisted Tomography , and AJR described a share of 31.5% FA and 22.1% SA in 2014 [ 10 ]. For European Radiology , 35.0% FA and 18.0% SA were described for 2016 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in an analysis from 2011 to 2015 of the medium- to high-ranked journals Radiology , Academic Radiology , and AJR, Campbell et al [ 7 ] attributed 30% of FA and 25% of SA to women. A study of the four medium- to high-ranking journals Radiology , EJR, Journal of Computer Assisted Tomography , and AJR described a share of 31.5% FA and 22.1% SA in 2014 [ 10 ]. For European Radiology , 35.0% FA and 18.0% SA were described for 2016 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both, the demonstrated general publication gap and the reduced proportions of female senior authors in high-ranked journals are likely to have consequences on female careers. Less authorships in high-ranked journals contribute to lower citation rates of female authors [ 10 ] and thus a lower h-index and academic progress. This relation is supported by a study, which showed that after multivariable adjustment of publication counts and NIH funding rates, full professorship among male and female radiologists was not significantly different [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the feminization of the workforce in medicine, women do not have the same career perspectives or pay as men (1)(2)(3)(4). In the field of medical imaging, the 'pipeline' to the top positions has been described as leaky for female talent, and leadership positions are predominantly held by men (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the gender imbalance in the number of women in senior positions and amongst tenure-track faculty members, some studies have also reported a citation advantage for male-last authored papers in biomedical and life sciences fields [ 7 9 ]. However, some others did not find notable differences between male and female-last authored papers or between female and male authors in terms of the number received citations [ 10 , 11 ]. Typically, in biomedicine, the author listed first has less experience and does most of the research work, while the author listed last has more experience and provides a supervisory role [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%